2015
DOI: 10.1016/j.yjmcc.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial remodeling in mice with cardiomyocyte-specific lipid overload

Abstract: Background Obesity leads to metabolic heart disease (MHD) that is associated with a pathologic increase in myocardial fatty acid (FA) uptake and impairment of mitochondrial function. The mechanism of mitochondrial dysfunction in MHD, which results in oxidant production and decreased energetics, is poorly understood but may be related to excess FAs. Determining the effects of cardiac FA excess on mitochondria can be hindered by the systemic sequelae of obesity. Mice with cardiomyocyte-specific overexpression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 57 publications
0
44
1
Order By: Relevance
“…Increasing expression of PDK4 in the heart itself has not been reported to be pathologic in vivo [45] and has been shown to trigger an adaptive metabolic response [46]. Alterations in mitochondrial size and lipid accumulation have been associated with increased PPARα activation [47]. However, no changes in mitochondrial number and only minimal qualitative alterations were identified in MuRF1−/− hearts post-fenofibrate feeding up to 8 weeks (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing expression of PDK4 in the heart itself has not been reported to be pathologic in vivo [45] and has been shown to trigger an adaptive metabolic response [46]. Alterations in mitochondrial size and lipid accumulation have been associated with increased PPARα activation [47]. However, no changes in mitochondrial number and only minimal qualitative alterations were identified in MuRF1−/− hearts post-fenofibrate feeding up to 8 weeks (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other lipid metabolism intermediates, namely diacylglycerols (DAGs) and ceramides, have been shown to interact with the insulin signalling pathway (Figure ), and their accumulation might lead to metabolic disturbances. The accumulation of DAGs increases protein kinase C (PKC)‐θ and PKC‐ε translocation in heart, following the reduction of Akt phosphorylation and decreased expression of mitochondrial fusion mediators . Ceramides inhibit Akt signalling via increased protein phosphatase 2 activity and activation of atypical PKC‐ζ .…”
Section: Pathophysiology Of Disturbances In Mitochondrial Metabolismmentioning
confidence: 99%
“…A reduction in cardiac phosphocreatine/ATP ratios has also been demonstrated in hearts of diabetic patients with normal cardiac function by echocardiography [66, 67], suggesting that changes in mitochondrial function may precede the reduction in contractility. In another study, Anderson et al demonstrated in the left atrial appendage tissue from Type 2 diabetic patients undergoing coronary bypass surgery that mitochondrial respiratory function was impaired and hydrogen peroxide emission was increased, suggesting an increase in oxidative stress [68, 69]. Together with human data demonstrating altered lipid metabolism, these studies strongly implicate mitochondrial dysfunction in the human diabetic heart.…”
Section: Mitochondrial Dysfunction In Diabetic Heartmentioning
confidence: 99%